ARKADIUSZ URBANEK, SYSTEM PENITENCJARNY WOBEC WYZWAŃ WIELOKULTUROWOŚCI – STUDIUM DIAGNOSTYCZNE, OFICYNA WYDAWNICZA IMPULS, KRAKÓW 2018, S. 278 - Rogalska-Marasińska, Aneta (Rocznik Pedagogiczny, 2018)
brak